WARUNG KOPI, MASYARAKAT VIRTUAL, DAN HIPEREALITAS (KETIKA WARUNG KOPI MENGABURKAN BATASAN REALITA) - putri Maulina (Universitas Teuku Umar, 2018)
The phenomenon of coffee shops that have been prevalent in Aceh go hand in hand with thedevelopment of communication and information technology. The existence of a coffee shop thatused to describe the miniaturized social interaction of the people of Aceh in a conventional way,now shifts its meaning as a means of reflecting the modernity of contemporary Acehnesesociety. The purpose of this study is to see how the shift in the meaning of the reality of coffeeshops to contemporary Acehnese society. The theoretical and conceptual approaches used toexamine the problems are: the Hiperealitas concept by Jean Baudrillard, and The OnlineDisinhibition Effect Theory by John Suler. This study is qualitative descriptive, using literaturereview method as data collection and analysis technique. The results of the study illustrate that:(1) the reality in the coffee shop is one part of the sign hypereality in the contemporary socioculturalcontext of Acehnese society (2) the disinhibtion behavior of the Acehnese community incyberspace can also be formed from the intensity of activity in the coffee shop with free internetfacility, and (3) the Acehnese community is a consumer society with 'ecstasy' of virtualsimulations obtained from coffee shops.Keywords : Hyper-reality, Virtual Community, Consumerisme, Consumer Society